Antipsychotic Drug Development: From Historical Evidence to Fresh Perspectives - Weston-Green, Katrina (Frontiers in Psychiatry, 2022)
Schizophrenia is a complex disorder of varied aetiology, manifesting symptoms that can differ between patients and change throughout an individual’s lifespan. Antipsychotic drugs have evolved through first (eg haloperidol), second (olanzapine and clozapine) and a possible third (aripiprazole) generation of drugs in an attempt to improve efficacy and tolerability, with minimal side-effects. Despite robust scientific efforts over the past 70 years, there remains a need to develop drugs with greater efficacy, particularly in relation to the negative and cognitive symptoms of schizophrenia, addressing treatment resistance, with a lower side-effects profile compared to existing antipsychotic drugs. Identifying and investigating novel therapeutic targets remains an important component of future antipsychotic drug discovery; however, mounting evidence demonstrates neurobiological, neuroanatomical and functional heterogeneity in cohorts of individuals with schizophrenia. This presents an opportunity to refresh the approach to drug trials to a more targeted strategy. By increasing understanding of the basic science and pharmacological mechanisms underlying the potential antipsychotic efficacy of novel therapeutics prior to clinical trials, new drugs may be appropriately directed to a target population of schizophrenia subjects based on the drug mechanisms and correlating biological sub-groupings of patient characteristics. Improving the lives of sub-populations of people with schizophrenia that share common biological characteristics and are likely to be responsive to a particular compound may be more achievable than aiming to treat the complexities of schizophrenia as a homogenous disorder. This approach to clinical trials in antipsychotic research is discussed in the present review.